Answer:
1). y= -5+3x
2). y= -2x-13
3). y= -6x+2
4). y= -x+4
5). y≈ 0.57x
6). y=2x-9
7). Equation incomplete
8). y=3x+23
Step-by-step explanation:
1).
3x-y=5
Subtract 3x from both sides
-y=5-3x
Multiply both sides by -1
y= -5+3x
2).
y+7= -2(x+3)
y+7= -2x-6
Subtract 7 from both sides
y= -2x-13
3).
y= -10-6(x-2)
y= -10-6x+12
y= -6x+2
4).
3x=12-3y
Add 3y to both sides
3x+3y=12
Subtract 3x from both sides
3y=12-3x
Divide both sides by 3
y= -x+4
5).
-4x-7y=0
Add 4x to both sides
-7y= -4x+0
Multiply both sides by -1
7y= 4x
Divide both sides by 7
y≈ 0.57x
6).
4x-2y=18
Subtract 4x from both sides
-2y= -4x+18
Multiply both sides by -1
2y=4x-18
Divide both sides by 2
y=2x-9
7).
y= 5-
Equation is incomplete.
8).
y-2=3(x+7)
y-2=3x+21
Add 2 to both sides
y=3x+23